Differential contribution of education through KIR2DL1, KIR2DL3, and KIR3DL1 to antibody-dependent (AD) NK cell activation and ADCC. Issue 3 (30th January 2019) - Lisovsky, Irene; Kant, Sanket; Tremblay-McLean, Alexandra; Isitman, Gamze; Kiani, Zahra; Dupuy, Franck P; Gilbert, Louise; Bruneau, Julie; Shoukry, Naglaa H; Lebouché, Bertrand; Bernard, Nicole F
Abstract: The engagement of activating NK receptors (aNKR) stimulates NK cell activity, provided that interactions between inhibitory NK receptors (iNKR) with their HLA ligands do not override them. Abs bound to target cells can also activate NK cells by engaging the CD16 aNKR. NK cell education status is an important factor for Ab-dependent NK cell activation (ADNKA) of some NK cell subsets. However, whether NK cell education also influences Ab-dependent cellular cytotoxicity (ADCC) levels is not fully known. ADCC-GranToxiLux (GTL) assays measured ADCC activity as the frequency of granzyme B positive (%GzB + ) target cells. Target cells were anti-HIV Immunoglobulin G (HIVIG)-opsonized CEM-NKr.CCR5 (CEM) cells. Lymphocytes and sorted single positive (SP) NKG2A +, KIR2DL1 +, KIR2DL3 +, and KIR3DL1 + NK cells, to self- and nonself HLA, were used as effectors in ADCC-GTL assays to examine how education status influenced ADCC activity. ADNKA activity was assessed by stimulating lymphocytes with HIVIG-opsonized CEMs and measuring the frequency of NK cell populations defined by their expression of iNKRs, along with IFN-γ, CCL4, and CD107a functions. ADCC: the %GzB + CEM cells generated by self- versus nonself HLA-specific SPiNKR did not differ. ADNKA: More NK cells educated through KIR2DL1 and KIR3DL1, but not KIR2DL3, responded to ADNKA than their uneducated counterparts. CD16 engagement induced ADCC and ADNKA activity. With the proviso that groups' sizes were small, our results support the notion that NK cell education does not influence ADCC levels but does contribute to ADNKA activity. Graphical Abstract: NK cell education through inhibitory Killer Immunoglobulin-like Receptors activates antibody-dependent NK cell functions but mediate antibody-dependent cellular cytotocitiy no better than their uneducated counterparts.